ӨНДӨРНАРАНГИЙН ТАЛБАЙ ДАХЬ АЛТ-ЗЭСИЙН ХҮДЭРЖИЛТИЙН ОНЦЛОГ - Б.ТАМИР (Geological Issues, 2023)
Undurnaran survey area is situated in the northeast of the South Mongolian fold province and the northwest of the Zuunbayan depression. This paper summarizes geological characteristics and mineralization types of Au-Cu porphyry deposits and occurrences revealed by recently conducted survey projects within the interest area. The porphyry and dikes identified within the exploration area mostly occur as sulfide and oxidation ore minerals, veins and inclusions produced by metasomatism of Dushin Ovoo and Gunbayan formation volcanogenic and terrigenous rocks and Undurnaran intrusive rocks which intrude the previously named formation. There have been discovered single Au deposit, a couple of Au occurrences and a couple of Cu mineralization occurrences so far.